Biochemical investigation of human tumours in vivo with phosphorus-31 magnetic resonance spectroscopy. - Oberhaensli, R; Hilton-Jones, D; Bore, P; Hands, L; Rampling, R; Radda, G (1986)
The bioenergetic state of 15 human tumours was examined with phosphorus-31 magnetic resonance spectroscopy. A striking diversity in metabolic patterns was observed, and significant differences from normal tissue were seen in all cases. A common feature was an elevation of intracellular pH, which may be related to an increase in Na+/H+ exchange during cell activation. It is unlikely that the patterns observed directly correlate with malignancy, but characterisation of the energetic state of a given tumour in a given physiological environment may help in the design and evaluation of interventions for that specific case.